2002
DOI: 10.1007/bf03214838
|View full text |Cite
|
Sign up to set email alerts
|

Microchemical Characterization of Alluvial Gold Grains as an Exploration Tool

Abstract: There is considerable variation in the composition of native gold and the nature of minerals co-existing with it, and this reflects differences in the geological environment and chemistry of ore-forming processes. In areas where gold-bearing mineralization is subject to active fluvial erosion, especially in temperate climatic regimes, any discrete grains of native gold pass into alluvial sediment with little modification. The chemical characteristics of alluvial grains and the nature of preserved mineral inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
0
20
1
5
Order By: Relevance
“…The textures associated with deposition of authigenic gold are evident in polished section when grains are examined by SEM and have not been observed in any of 5290 grains examined from Great Britain and Ireland during the studies of Leake et al (1997Leake et al ( , 1998 and Chapman et al (2000aChapman et al ( ,b, 2005. Neither has any evidence for gold grains which are entirely authigenic been observed in the Klondike District, Yukon Territory in studies by Knight et al (1999a) or by Chapman et al (2002). Consequently there is no evidence that the placer gold populations studied here have been modified by the addition of authigenic grains.…”
Section: Discrimination Between Epithermal and Authigenic Goldcontrasting
confidence: 61%
See 2 more Smart Citations
“…The textures associated with deposition of authigenic gold are evident in polished section when grains are examined by SEM and have not been observed in any of 5290 grains examined from Great Britain and Ireland during the studies of Leake et al (1997Leake et al ( , 1998 and Chapman et al (2000aChapman et al ( ,b, 2005. Neither has any evidence for gold grains which are entirely authigenic been observed in the Klondike District, Yukon Territory in studies by Knight et al (1999a) or by Chapman et al (2002). Consequently there is no evidence that the placer gold populations studied here have been modified by the addition of authigenic grains.…”
Section: Discrimination Between Epithermal and Authigenic Goldcontrasting
confidence: 61%
“…Townley et al (2003) produced compositional fields in terms of Au, Ag and Cu content for gold from some low and high sulphidation epithermal deposits and Cu-Au porphyry deposits in South America and southeast Asia. This approach is not diagnostic for the style of mineralization, however, since many lode gold occurrences of other styles investigated by Chapman et al (2000aChapman et al ( , 2002 exhibit compositions within the fields quoted. Additional valuable information regarding the origins of placer gold can be obtained from the study of the microinclusion assemblages of opaque and transparent minerals found within the gold grains.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The microchemical signature of gold grains from soils and alluvial environments can be modified by two processes: either by leaching within the aqueous environment or by the addition of authigenic gold (Chapman et al, 2002). Gold grains from the saprolite and laterite horizons in the Batouri gold district show Ag-depleted domains (Figs.…”
Section: Gold Microchemical Signaturementioning
confidence: 97%
“…The technique of microchemical classification of the placer gold grains (Chapman et al, ; Chapman, Leake, & Styles, ; Chapman, Mortensen, Crawford, & LeBarge, , ; Chapman et al, ; Chapman, Shaw, Leake, & Jackson, ; Lalomov et al, ; Leake et al, ; Moles et al, ; Omang et al, ) has been applied to illustrate the types of placer gold and their relations to the source mineralization, even in the cases, the lode source remains unknown. This technique provides important clues to predict the mode of source mineralization by comparing the microchemical signature of a population of placer gold grains with the generic characteristics of different modes of gold mineralization (Chapman & Mortensen, ).…”
Section: Discussionmentioning
confidence: 99%